KEPATUHAN PENGENDARA KENDARAAN BERMOTOR DI JALAN RAYA BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Siwalette, Nona D.; Handayati, Nur; Prawesthi, Wahyu (Gapenas Publisher, 2025)
This normative legal study analyzes the legal compliance of motor vehicle drivers within the context of Law No. 22 of 2009 concerning Road Traffic and Transport. The research focuses on the disruption between ideal norms and their real-world implementation, where low legal awareness and social factors are the main obstacles. This study asserts that compliance is not merely a civil obligation but an essential aspect of citizen participation in maintaining public order. The research delves into the mechanisms of law enforcement for traffic violations, ranging from administrative fines to criminal liability. It emphasizes that the effectiveness of regulations depends heavily on three pillars: the legal substance (the Law itself), the legal structure (enforcement institutions), and the legal culture (public awareness). The strategic recommendations from this study include the digital transformation of law enforcement through electronic ticketing (e-tilang), the optimization of progressive legal education, and the adaptation of regulations to keep pace with technological advancements and mobility. Overall, these findings underscore the urgency of multi-stakeholder synergy to ensure legal certainty and traffic safety